Perlindungan Hukum melalui Itsbat Nikah pada Poligami Siri: Tinjauan atas Putusan PA No. 43/Pdt.G/2021/PA.Batg - Muchlis, Muhammad; Purba, Hasim; Barus, Utary Maharany (JOM, 2025)
A valid marriage under Article 2 paragraph (1) of Law Number 1 of 1974 is one conducted in accordance with religious law, provided it does not contradict the Marriage Law. However, in practice, unregistered marriages, including polygamous ones, still occur and generate significant legal consequences, particularly in divorce cases. This study aims to examine the validity of itsbat nikah (marriage validation) for unregistered polygamous marriages within Indonesia’s positive law, to analyze its position as a form of legal protection for wives in divorce proceedings, and to evaluate judicial considerations in Religious Court Decision Number 43/Pdt.G/2021/PA.Batg. Using a normative juridical approach, supported by literature review and case analysis, this research finds that the rejection of itsbat nikah in this case was legally flawed. The absence of valid evidence of the husband’s first marriage led to the neglect of the wife’s rights. Article 71 of the Compilation of Islamic Law (KHI) clearly states that itsbat nikah is designed to acknowledge marriages valid under religion, even when unregistered, rather than to legitimize unlawful polygamy. These findings highlight the need for more consistent judicial interpretation to ensure the protection of women’s rights in unregistered polygamous marriages.